1957
DOI: 10.1021/i460002a008
|View full text |Cite
|
Sign up to set email alerts
|

Isopropyl Alcohol-Sodium Sulfate-Water System. Liquid-Liquid Equilibria.

Abstract: D uring t h e sulfonation of petroleum d i s t i l l a t e s for highly refined white o i l s , oil-soluble mahogany sulfonic a c i d s a r e obtained as a by-product i n t h e sour oil. T h i s oil may b e considered a heterogeneous system, a s it c o n t a i n s some of the s p e n t sulfuric acid not separated with t h e a c i d sludge p h a s e and t r a c e s of sulfur dioxide formed by redox s i d e reactions. T h e corresponding sodium s o a p may b e obtained a s a crude product by neutralization with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1966
1966
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…Their SLL equilibrium data at 353.15 K are represented in Figure 2. Mills and Smith [16] also determined liquid-liquid equilibrium data for the system with 2-propanol at 313.15 and 333.15 K. As in the systems with K2SO4, the temperatures used in the present work are higher than those but follow the trends of the previous data within the uncertainty of the measurements as can be seen in Figure . In previous works, the equilibrium diagrams of water + NaCl/KCl/NH4Cl + 1-propanol or 2propanol systems [7][8][9][10][11] were determined at boiling temperatures and 101.3 kPa. All these systems, where monovalent salts were involved, showed liquid-liquid phase splitting at the boiling point and even at lower temperatures, giving rise to ATPSs.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…Their SLL equilibrium data at 353.15 K are represented in Figure 2. Mills and Smith [16] also determined liquid-liquid equilibrium data for the system with 2-propanol at 313.15 and 333.15 K. As in the systems with K2SO4, the temperatures used in the present work are higher than those but follow the trends of the previous data within the uncertainty of the measurements as can be seen in Figure . In previous works, the equilibrium diagrams of water + NaCl/KCl/NH4Cl + 1-propanol or 2propanol systems [7][8][9][10][11] were determined at boiling temperatures and 101.3 kPa. All these systems, where monovalent salts were involved, showed liquid-liquid phase splitting at the boiling point and even at lower temperatures, giving rise to ATPSs.…”
Section: Resultssupporting
confidence: 54%
“…Therefore, the equilibrium diagrams of the water + Na2SO4/K2SO4 + 1-propanol/2-propanol systems have been determined at boiling temperatures and 101.3 kPa. No studies of the equilibrium of these four systems at boiling temperatures have been found in the literature although there are several works with equilibrium determinations at lower temperatures [12][13][14][15][16] 2. Experimental…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the precipitation at 65 °C of an aqueous solution by isopropanol was investigated. However, in these conditions, the aqueous and organic phases are not miscible 32 and precipitation does not occur. Instead, the water in the aqueous fraction evaporates, leading to a mixture of Na 2 Fe(SO 4 ) 2 •4H 2 O and FeSO 4 •H 2 O.…”
Section: Precursor Designmentioning
confidence: 99%
“…Solubility of sodium sulfate in isopropanol-water system was reported by Mills and Smith. 16 Assuming that the SCG residue in the solid residue after neutralization (Residue #2) will generate the same amount of ash (3.8% AE 0.2%) measured for SCG residue after extraction of the liquefaction product with isopropanol (Table 1), 5.1 g of total Residue #2 weight (56.7 g) can be ascribed to sodium sulfate. The remaining amount of 51.6 g can be ascribed to the dry solid residue after liquefaction reaction that was removed with the isopropanol during the decantation process.…”
Section: Acid Liquefaction Of Scg and Characterization Of Solid Residuesmentioning
confidence: 94%